Clinical characteristics of patients with familial idiopathic pulmonary fibrosis (f-IPF) - Ekaterina Krauss; Godja Gehrken; Fotios Drakopanagiotakis; Silke Tello; Ruth C. Dartsch; Olga Maurer; Anita Windhorst; Daniel von der Beck; Matthias Griese; Werner Seeger; Andreas Guenther (BMC Pulmonary Medicine, 2019)
Abstract Background The aim of this study was to analyze the relative frequency, clinical characteristics, disease onset and progression in f-IPF vs. sporadic IPF (s-IPF). Methods Familial IPF index patients and their family members were recruited into the European IPF registry/biobank (eurIPFreg) at the Universities of Giessen and Marburg (UGMLC). Initially, we employed wide range criteria of f-IPF (e.g. relatives who presumably died of some kind of parenchymal lung disease). After narrowing down the search to occurrence of idiopathic interstitial pneumonia (IIP) in at least one first grade relative, 28 index patients were finally identified, prospectively interviewed and examined. Their family members were phenotyped with establishment of pedigree charts. Results Within the 28 IPF families, overall 79 patients with f-IPF were identified. In the same observation period, 286 f-IIP and s-IIP patients were recruited into the eurIPFreg at our UGMLC sites, corresponding to a familial versus s-IPF of 9.8%. The both groups showed no difference in demographics (61 vs. 79% males), smoking history, and exposure to any environmental triggers known to cause lung fibrosis. The f-IPF group differed by an earlier age at the onset of the disease (55.4 vs. 63.2 years; p < 0.001). On average, the f-IPF patients presented a significantly milder extent of functional impairment at the time point of inclusion vs. the s-IPF group (FVC 75% pred. vs. FVC 62% pred., p = 0.011). In contrast, the decline in FVC was found to be faster in the f-IPF vs. the s-IPF group (4.94% decline in 6 months in f-IPF vs. 2.48% in s-IPF, p = 0.12). The average age of death in f-IPF group was 67 years vs. 71.8 years in s-IPF group (p = 0.059). The f-IIP group displayed diverse inheritance patterns, mostly autosomal-dominant with variable penetrance. In the f-IPF, the younger generations showed a tendency for earlier manifestation of IPF vs. the older generation (58 vs. 66 years, p = 0.013). Conclusions The 28 f-IPF index patients presented an earlier onset and more aggressive natural course of the disease. The disease seems to affect consecutive generations at a younger age. Trial registration Nr. NCT02951416 http://www.www.clinicaltrials.gov